(untitled) (Dhaka University Journal of Biological Sciences, 2019)
Bipolaris sorokiniana (Sacc.) Shoemaker is a phytopathogenic fungus, causal agent of leaf blight disease of wheat. This fungus is difficult to control because of its immense cultural, morphological, physiological, pathogenic and genetic variability. The aim of this investigation was to study the cultural variability of the selected isolates of B. sorokiniana by means of mycelial compatibility. One hundred fifty isolates of B. sorokiniana from eight districts (Dhaka, Gazipur, Dinajpur, Joypurhat, Pabna, Sirajgonj, Kushtia and Chuadanga) of Bangladesh were studied and cultural variation was characterized on the basis of colony color and texture on PDA medium. They were - Black-Mat (B-M), Black-Fluffy (B-F), Ash-Mat (A-M), Brownish Ash-Fluffy (Br. A-F), Blackish Ash-Mat (Bl.AM), Whitish Ash-Mat (W. A-M), Greenish Ash-Fluffy (G. A-F) and Pinkish White-Mat (P.W-M). To compare and understand cultural variability, mycelial compatibility test was done among the cultural groups. Results revealed that selected isolates of different cultural groups showed incompatible reaction. Incompatibility was also noticed between the isolates of same district and different districts. Dhaka Univ. J. Biol. Sci. 28(2): 195-209, 2019 (July)